The reproductive toxicity of CdSe/ZnS quantum dots on the in vivo ovarian function and in vitro fertilization - Xu, Gaixia (2018)
Despite the usefulness of quantum dots (QDs) in biomedicine and optoelectronics, their toxicity risks remain a major obstacle for clinical usages. Hence, we studied the reproductive toxicity of CdSe/ZnS QDs on two aspects, (i) in vivo ovarian functions and (ii) in vitro fertilization process. The body weight, estrous cycles, biodistribution of QDs, and oocyte maturation are evaluated on female mice treated with QDs. The mRNA level of the follicle-stimulating hormone receptor (FSHr) and luteinizing hormone receptor (LHr) in ovaries are assayed. Then, the matured cumulus-oocyte-complexes are harvested to co-culture with in vitro capacitated sperms, and the in vitro fertilization is performed. The result revealed that QDs are found in the ovaries, but no changes are detected on the behavior and estrous cycle on the female mice. The mRNA downregulations of FSHr and LHr are observed and the number of matured oocytes has shown a significant decrease when the QDs dosage was above 1.0 pmol/day. Additionally, we found the presence of QDs has reduced the in vitro fertilization success rate. This study highly suggests that the exposure of CdSe/ZnS QDs to female mice can cause adverse effects to the ovary functions and such QDs may have limited applications in clinical usage.